Self-Assembly of Fibrinogen in Aqueous, Thrombin-Free Solutions of Variable Ionic Strengths - Hämisch, Benjamin; Büngeler, Anne; Kielar, Charlotte; Keller, Adrian; Strube, Oliver; Huber, Klaus (Langmuir)

Invertible Micelles Based on Ion-Specific Interactions of Sr2+ and Ba2+ with Double Anionic Block Copolyelectrolytes - Carl, Nico; Prévost, Sylvain; Schweins, Ralf; Houston, Judith E.; Morfin, Isabelle; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Phase Transformation Behavior of Polylactide Probed by Small Angle Light Scattering and Calorimetry - Schmidt, Nico; Keuker‐Baumann, Susanne; Meyer, Jörg; Huber, Klaus (Journal of Polymer Science Part B: Polymer Physics)
Keywords: Materials Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics

Controlling Self-Assembly with Light and Temperature - Carl, Nico; Müller, Wenke; Schweins, Ralf; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

On Protein Folding in Crowded Conditions - Gomez, David; Huber, Klaus; Klumpp, Stefan (The Journal of Physical Chemistry Letters)
Keywords: General Materials Science; Physical and Theoretical Chemistry

Ion-selective binding as a new trigger for micellization of block copolyelectrolytes with two anionic blocks - Carl, Nico; Prévost, Sylvain; Schweins, Ralf; Huber, Klaus (Soft Matter)
Selective binding of Ca2+ cations to block copolyelectrolytes with two anionic blocks yields well-defined micelles.
Keywords: Condensed Matter Physics; General Chemistry

Self-Assembly of Fibrinogen in Aqueous, Thrombin-Free Solutions of Variable Ionic Strengths - Hämisch, Benjamin; Büngeler, Anne; Kielar, Charlotte; Keller, Adrian; Strube, Oliver; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Effect of ionic strength on the structure and elongational kinetics of vimentin filaments - G. Lopez, Carlos; Saldanha, Oliva; Aufderhorst-Roberts, Anders; Martinez-Torres, Cristina; Kuijs, Merel; Koenderink, Gijsje H.; Köster, Sarah; Huber, Klaus (Soft Matter)
The present work characterizes the assembly process of vimentin intermediate filaments with monovalent salts as an assembly trigger. A multi-scale approach is used, comprising time-resolved static and dynamic light scattering and quantitative scanning transmission electron microscopy.
Keywords: Condensed Matter Physics; General Chemistry

Liquid-liquid phase separation in dilute solutions of poly(styrene sulfonate) with multivalent cations: Phase diagrams, chain morphology, and impact of temperature - Hansch, Markus; Hämisch, Benjamin; Schweins, Ralf; Prévost, Sylvain; Huber, Klaus (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Polyacrylates in the presence of an extraordinary monovalent cation—Solution behavior and metal nanoparticle formation - Urbanski, Anna; Hansch, Markus; Lopez, Carlos G.; Schweins, Ralf; Hertle, Yvonne; Hellweg, Thomas; Polzer, Frank; Huber, Klaus (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Insight into Fast Nucleation and Growth of Zeolitic Imidazolate Framework-71 by In Situ Static Light Scattering at Variable Temperature and Kinetic Modeling - Saha, Sanjib; Wiebcke, Michael; Huber, Klaus (Crystal Growth & Design)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Reaction enthalpy from the binding of multivalent cations to anionic polyelectrolytes in dilute solutions - Hansch, Markus; Kaub, Hans Peter; Deck, Sascha; Carl, Nico; Huber, Klaus (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Secondary Particle Formation during the Nonaqueous Synthesis of Metal Oxide Nanocrystals - Stolzenburg, Pierre; Hämisch, Benjamin; Richter, Sebastian; Huber, Klaus; Garnweitner, Georg (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Silica Polymerization from Supersaturated Dilute Aqueous Solutions in the Presence of Alkaline Earth Salts - Kley, M.; Kempter, A.; Boyko, V.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Insight into the Final Step of the Supramolecular Buildup of Eumelanin - Büngeler, Anne; Hämisch, Benjamin; Huber, Klaus; Bremser, Wolfgang; Strube, Oliver I. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Lateral association and elongation of vimentin intermediate filament proteins: A time-resolved light-scattering study - Lopez, Carlos G.; Saldanha, Oliva; Huber, Klaus; Köster, Sarah (Proceedings of the National Academy of Sciences)
Significance The hierarchical assembly pathway of the cytoskeletal protein vimentin may be responsible for the astonishing mechanical properties of the emerging filaments, such as high flexibility and extensibility, and thus play a key role in cellular mechanics. A two-step assembly mechanism, involving a lateral and a subsequent elongational step, has been established; however, the elongational step could not be followed in solution. Here, we show direct in situ observation and modeling of the elongation reaction of the filaments on the relevant length and time scales, using time-resolved, multiangle static and dynamic light scattering. We thus achieve sufficient spatio-temporal resolution without the need of labeling, staining, or adsorption to substrates.
Keywords: Multidisciplinary

Insight into Fast Nucleation and Growth of Zeolitic Imidazolate Framework-71 by In Situ Time-Resolved Light and X-ray Scattering Experiments - Saha, Sanjib; Springer, Sergej; Schweinefuß, Maria E.; Pontoni, Diego; Wiebcke, Michael; Huber, Klaus (Crystal Growth & Design)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Contraction and Coagulation of Spherical Polyelectrolyte Brushes in the Presence of Ag+, Mg2+, and Ca2+ Cations - Ezhova, Anna; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Systematic Limitations in Concentration Analysis via Anomalous Small-Angle X-ray Scattering in the Small Structure Limit - Goerigk, Guenter; Lages, Sebastian; Huber, Klaus (Polymers)
Keywords: Polymers and Plastics; General Chemistry

Metastable metal imidazolates: development of targeted syntheses by combining experimental and theoretical investigations of the formation mechanisms - Schröder, Christian A.; Saha, Sanjib; Huber, Klaus; Leoni, Stefano; Wiebcke, Michael (Zeitschrift für Kristallographie - Crystalline Materials)
Abstract In this report, we summarize our experimental and theoretical investigations in the zinc(II) imidazolate, [Zn(im) 2 ], and zinc(II) 4,5-dichloroimidazolate, [Zn(dcim) 2 ], systems that have been published previously. This comprises a study on the thermodynamic stabilities of the two densest phases with coi and zni framework structures in the [Zn(im) 2 ] system including the discovery and characterization of a new [Zn(im) 2 ·0.5py]-neb phase (py = pyridine), a study on the mechanism of formation of the [Zn(im) 2 ]-zni phase as well as a study on the discovery and characterization of a new [Zn(dcim) 2 ]-SOD phase. In addition, we present as yet unpublished work. This concerns the discovery and characterization of a new [Zn(im) 2 ·0.5mor]-neb phase (mor = morpholine) and investigations of the mechanisms of crystallization of [Zn(im) 2 ·0.5py]-neb and [Zn(im) 2 ·0.5mor]-neb as well as an evalutation of time-resolved SAXS/WAXS data recorded in-situ during the formation of [Zn(im) 2 ]-zni.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science